Dian and the Gorillas : a true story - Shapiro, Norma (Oxford University Press, 2010)
Content: Over the years hunters, poachers, and war have killed many of the gorillas of central Africa. But there are still a few hundred living high in the mists of the Virunga Mountains. When Dian Fossey first saw a family of wild mountain gorillas in the Virungas she knew that she must help these wonderful animals. This true story tells of the twenty years she lived with them, watched them, wrote about them, and protected them. In the end, she gave her life for them.